Assessment of spinal alignment in children with unilateral cerebral palsy. (December 2022) - Porsnok, Doğan; Mutlu, Akmer; Livanelioğlu, Ayşe
Abstract: Background: Children/youths with unilateral cerebral palsy are at high risk for the development of scoliosis and other postural deformities. The purpose of this study was to perform spinal assessment in the frontal and sagittal plane using Spinal Mouse® in children/youths with unilateral cerebral palsy and to compare their spinal shape and angles with typically developing children/youths. Methods: 25 children/youths with unilateral cerebral palsy and 25 typical children/youths, aged 6–18 years, were included. The subject's frontal (scoliosis) and sagittal plane (kyphosis and lordosis) spinal curvatures were compared by assessing them with Spinal Mouse®. Findings: Scoliosis was detected in 40% of subjects in the unilateral cerebral palsy group and this rate was considerably higher than that in typical subjects (12%). The median angle of scoliosis was 8° in subjects with unilateral cerebral palsy and 5.3° in typical subjects. While the median angle of scoliosis was higher in subjects with unilateral cerebral palsy than typical subjects ( p < 0.001), there was no significant difference in the angles of lordosis and kyphosis between both groups ( p > 0.05). Curvature patterns of subjects with unilateral cerebral palsy differed from typical subjects. Interpretation: Our findings will allow children/youths with unilateral cerebral palsy, who are at risk of developing spinal deformity, to be identified earliest possible and included in the intervention. Children/youths with unilateral cerebral palsy have to be assessed in detail from the earliest period, especially when the possibility of an age-related increase in scoliosis is considered. Highlights: Asymmetry in unilateral cerebral palsy may cause various postural deformities. Scoliosis was observed in 40% of unilateral cerebral palsy children/youths. Children/youths with unilateral cerebral palsy with scoliosis were older. Kyphosis and lumbar lordosis angles were similar in both groups.